Microgravity-Induced Transcriptome Adaptation in Mouse Paraspinal longissimus dorsi Muscle Highlights Insulin Resistance-Linked Genes - Gambara, Guido; Salanova, Michele; Ciciliot, Stefano; Furlan, Sandra; Gutsmann, Martina; Schiffl, Gudrun; Ungethuem, Ute; Volpe, Pompeo; Gunga, Hanns-Christian; Blottner, Dieter (Frontiers in Physiology, 2017)
Microgravity as well as chronic muscle disuse are two causes of low back pain originated at least in part from paraspinal muscle deconditioning. At present no study investigated the complexity of the molecular changes in human or mouse paraspinal muscles exposed to microgravity. The aim of this study was to evaluate longissimus dorsi adaptation to microgravity at both morphological and global gene expression level. C57BL/N6 male mice were flown aboard the BION-M1 biosatellite for 30 days (BF) or housed in a replicate flight habitat on ground (BG). Myofiber cross sectional area and myosin heavy chain subtype patterns were respectively not or slightly altered in longissimus dorsi of BF mice. Global gene expression analysis identified 89 transcripts differentially regulated in longissimus dorsi of BF vs. BG mice. Microgravity-induced gene expression changes of lipocalin 2 (Lcn2), sestrin 1(Sesn1), phosphatidylinositol 3-kinase, regulatory subunit polypeptide 1 (p85 alpha) (Pik3r1), v-maf musculoaponeurotic fibrosarcoma oncogene family protein B (Mafb), protein kinase C delta (Prkcd), Muscle Atrophy F-box (MAFbx/Atrogin-1/Fbxo32) and Muscle RING Finger 1 (MuRF-1) were further validated by real time qPCR analysis. In conclusion, our study highlighted the regulation of transcripts mainly linked to insulin sensitivity and metabolism in longissimus dorsi following 30 days of microgravity exposure. The apparent absence of robust signs of back muscle atrophy in space-flown mice, despite the overexpression of Atrogin-1 and MuRF-1, opens new questions on the possible role of microgravity-sensitive genes in the regulation of peripheral insulin resistance following unloading and its consequences on paraspinal skeletal muscle physiology.